Design and Optimization of Sustained-Release Dental Implants for Targeted Periodontal Drug Delivery - Silpi Chatterjee; Daya Shankar; Yagyesh Mehta; Swamini Ajay Shete; Asim Mustafa Khan; Ankita Kumari (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontal therapy often requires sustained and targeted drug delivery to enhance therapeutic outcomes and minimize systemic side effects. Conventional methods, such as systemic administration and local application, often fail to maintain effective drug concentrations in periodontal pockets. Materials and Methods: This study involved the fabrication of sustained-release dental implants composed of biocompatible polymers incorporating antimicrobial agents. Polylactic-co-glycolic acid (PLGA) was used as the primary polymer matrix, and metronidazole was selected as the model drug. Implants were prepared using solvent evaporation techniques and optimized for drug release by altering polymer-to-drug ratios. Characterization of the implants was conducted through scanning electron microscopy (SEM) for surface morphology, differential scanning calorimetry (DSC) for thermal stability, and Fourier-transform infrared spectroscopy (FTIR) for chemical compatibility. Drug release kinetics were analyzed using an in vitro setup mimicking periodontal conditions over 30 days. Results: The optimized implants exhibited smooth surfaces with uniform drug distribution. The cumulative drug release profile demonstrated a sustained release of 85% ± 2% of the drug over 30 days, with an initial burst release of 10% ± 1% within the first 24 hours. FTIR and DSC analyses confirmed no chemical interactions or degradation of the drug within the polymer matrix. In vitro antimicrobial efficacy tests showed a zone of inhibition of 18 ± 1 mm against Porphyromonas gingivalis for 25 days. Conclusion: The designed sustained-release dental implants demonstrated excellent potential for targeted periodontal drug delivery, achieving prolonged drug release and effective antimicrobial activity. This approach offers a promising alternative for improving the management of periodontal diseases, reducing systemic drug exposure, and enhancing patient compliance.